Potensi Financial Distress pada Bank Umum Berbasis RGEC - Deranika Ratna Kristiana; Nada Devita Limbong; Atika Jauharia Hatta (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to analyze the effect of RGEC-based commercial bank soundness on potential financial distress. The independent variables in this study are NPL, LDR, Number of Board of Commissioners, Audit Committee Size, ROA, ROE and CAR, while the dependent variable in this study is financial distress as measured by the Bankometer method. The objects used in this study are commercial banks listed on the IDX and the publication of their financial statements for the period 2018 – 2020. The sampling technique in this study uses the purposive sampling method. The sample in this study was obtained by 40 commercial banks with 120 reports, but because there were 5 outlier data, only 115 financial statements were used as samples in the study. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that the variables NPL, ROE and CAR have a negative and significant effect on the potential for financial distress. The LDR, Audit Committee Size and ROA variables do not affect the potential for financial distress. The variable number of the Board of Commissioners has a positive and significant effect on the potential for financial distress. Keywords: Bank Soundness, Commercial Banks, RGEC, Financial Distress, Bankometer Method.